Assessing the Risk of Potential Tsunamigenic Earthquakes in the Mentawai Region by Seismic Imaging, Central Sumatra - Yanfang Qin; Jian Chen; Satish C. Singh; Nugroho Hananto; Helene Carton; Paul Tapponnier (Geochemistry, Geophysics, Geosystems, 2024)
Abstract In the marginal regions along subduction zones, oceanic plates subducting beneath continental plates produce the largest number of earthquakes on Earth and sometimes devastating tsunamis. The lateral segmentation of earthquakes along the Sumatra subduction zone is well documented. However, the entirely different seismic behaviors among the segments indicate that local structures are key elements controlling coseismic slip propagation; in particular, frontal accretionary prism structures are closely associated with tsunami generation. Offshore of Central Sumatra, in the Mentawai segment, large earthquakes nucleated in 2007 and 2010 caused many human casualties and a great deal of property loss. Using seismic reflection data, we show the subsurface structure of accretionary over a significant portion of the frontal wedge that did not rupture during the 2007 earthquake, and this area remains locked. The subsurface deformation structure at the wedge front, which is similar to that in the 2010 Mw7.8 tsunami earthquake rupture zone, suggests the potential for a large tsunami earthquake in the near future. On the other hand, the along‐strike variations of the effective basal friction at shallow depth may indicate that different coseismic behaviors are caused by a sudden failure of the deeper seismogenic zone.